Interaction of solar power satellite with the space and atmosphere environment - Diwan, Ritesh; Vaishnav, Divya (Recent Research in Science and Technology, 2014)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–> In this paper, we present the concept of transmitting power without using wires i.e., transmitting power as microwaves from one place to another is in order to reduce the transmission and distribution losses. This concept is known as Microwave Power transmission (MPT) using SOLAR POWER SATELLITE (SPS). This paper describes the SPS interaction with space and the atmosphere environment and influence of the SPS and MPT on human health and bio-effects; it also summarizes the advantages of the SPS. We also discussed the technological developments in solar power satellite. <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>